Peran Orangtua pada Keluarga Dalam Mencegah Covid-19 - Asmayanti Asmayanti; Ahmad Syarif; Eda Laelasari (EduInovasi: Journal of Basic Educational Studies, 2021)
The purpose of this study was to determine the role played by parents during the pandemic in preventing the spread of covid-19 to families. The research method used is qualitative with an exploratory case study design that is used to obtain information on the role of parents in the family in preventing Covid-19 transmission. In this study, respondents were 5 families in Depok. In order to achieve the objectives of this study, respondents were given the initials R1, R2, R3, R4, R5, interviews were developed based on related literature. Respondents for this study were parents from several families. The results of this study are that there are several obstacles experienced by parents, namely disciplining family members in undergoing health protocols and increasing costs for obtaining personal hygiene tools during the Covid-19 pandemic, as for the efforts that can be made in overcoming these problems are parents as guides, educators, carers, developers and supervisors. Specifically, it shows that the role of parents in preventing Covid-19 is to maintain and ensure that all family members adopt a clean and healthy lifestyle during the Covid-19 pandemic